Electrophoretic profile of serum proteins from Dromedary camels - CHOUDHARY, PREETI; CHANDRA, DINESH (The Indian Journal of Animal Sciences, 2014)
Electrophoretic pattern of serum protein and dialysed serum protein profiles were studied from apparently healthy camels on 10 and 15% SDS-PAGE in addition to total protein and immunoglobulin content. The electrophoretic pattern of camel serum protein revealed 7 prominent bands of molecular weights ranging from 28.21 kDa to 123.07 kDa on 10% SDS-PAGE and dialysed serum protein revealed 4 prominent bands of molecular weights ranging from 24.30 kDa to 110.87 kDa. The electrophoretic pattern of camel serum protein on 15% SDS PAGE revealed 8 prominent bands of molecular weights ranging from 0.005 to 121.04 kDa along with 5 bands of dialysed serum protein. There are about 7 lower molecular weight bands which may be of prealbumin and other lower molecular weights of proteins. The lower molecular weight bands may be of prealbumin. The band with higher molecular weight may be of different globulin fractions including immunoglobulins. Total protein and immunoglobulin content were low in present study suggesting that it is due to very hot temperature and limited grazing facility during summer.